Incidence of adverse events attributable to bupivacaine liposome injectable suspension or plain bupivacaine for postoperative pain in pediatric surgical patients: A retrospective matched cohort analysis. Issue 2 (31st December 2018) - Cohen, Barak; Glosser, Logan; Saab, Remie; Walters, Michael; Salih, Ahmed; Zafeer‐Khan, Mohammad; Rivas, Eva; Zhang, Kan; Schacham, Nadav Y.; Chodavarapu, Praneeta; Essber, Hani; Chelnick, David; et al.
Summary: Background: Surgical wound infiltration with local anesthetics is common as part of multimodal analgesia and enhanced recovery pathways in pediatric surgical patients. Liposomal bupivacaine can provide up to 92 hours of pain relief, and was approved by the U.S Food and Drug Administration for local infiltration in adults. It is also commonly used by pediatric surgeons, but its safety profile in this age group has not been described. Aims: The aim of this study was to describe the incidence of local anesthetic systemic toxicity syndrome in pediatric surgical patients receiving liposomal bupivacaine compared to plain bupivacaine for surgical wound infiltration. Methods: We conducted a retrospective, single center, assessor blinded cohort study of pediatric surgical inpatients having open or laparoscopic surgery in the Cleveland Clinic between 2013 and 2017 and receiving wound infiltration with local anesthetics. We compared the incidence of local anesthetic systemic toxicity among those who received any dose of liposomal bupivacaine and those who received plain bupivacaine. Groups were matched 1:2 according to procedure type, age, and physical status score. Local anesthetic systemic toxicity was primarily defined as at least two signs or symptoms possibly related to anesthetic toxicity, as judged by two independent adjudicators blinded to the type of local anesthetic. A sensitivity analysis compared the incidence of a single sign/symptom possibly related to anesthetic toxicity. Results: A total of 924 surgical cases were included in the final analysis (356 liposomal bupivacaine and 568 plain bupivacaine cases). The primary outcome did not occur in any patient. The sensitivity analysis found three cases in the liposomal bupivacaine group and two cases in the plain bupivacaine group having a single sign/symptom possibly related to local anesthetic administration (relative risk 2.4, 95% CI 0.4‐14.0, P  = 0.38). Conclusion: In a cohort of pediatric surgical patients receiving wound infiltration with either plain or liposomal bupivacaine, we identified no cases of local anesthetic systemic toxicity syndrome, and only few patients with any sign or symptom that could potentially be related to local anesthetic toxicity.